2016
DOI: 10.1590/1806-93042016000300005
|View full text |Cite
|
Sign up to set email alerts
|

The agreement between two screening tests for language evaluation in premature and low weight children

Abstract: Objectives: to evaluate the agreement of the results in two screening tests on children´s development -Denver II and Early Language Milestone Scale (ELM) aged two to three years old, born prematurely and with low weight.Methods: two screening instruments: Denver II and ELM were applied for the development in an observational cross-sectional descriptive study. The agreement between Denver II Test and its language sector and ELM were assessed by Kappa coefficient.Results: 77 children evaluated, 36.3% had an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…However, when the link between the sex of the children studied and child development is assessed, an association was not found, thus disagreeing with other findings in the literature, for example, a research that demonstrated that girls achieved performance better in three of the areas surveyed (social personnel, fine motor and language) and only in one of the areas (large motor) there was no statistically significant difference between females and males. 2 It can be seen, with regard to the type of delivery, in this study, that there was no significant statistical association, a fact that is in disagreement with the literature, since several authors pointed out that cesarean delivery is a risk factor for child development, as a study, 11 that evaluated 77 children aged two to three years, premature and of low weight, in the city of Cuiabá (MT), noting that children who were born by cesarean delivery had a 44.6% change in the Denver II test, with a predominance in language area.…”
Section: Resultscontrasting
confidence: 63%
“…However, when the link between the sex of the children studied and child development is assessed, an association was not found, thus disagreeing with other findings in the literature, for example, a research that demonstrated that girls achieved performance better in three of the areas surveyed (social personnel, fine motor and language) and only in one of the areas (large motor) there was no statistically significant difference between females and males. 2 It can be seen, with regard to the type of delivery, in this study, that there was no significant statistical association, a fact that is in disagreement with the literature, since several authors pointed out that cesarean delivery is a risk factor for child development, as a study, 11 that evaluated 77 children aged two to three years, premature and of low weight, in the city of Cuiabá (MT), noting that children who were born by cesarean delivery had a 44.6% change in the Denver II test, with a predominance in language area.…”
Section: Resultscontrasting
confidence: 63%
“…It is important to highlight that six studies included only children under two years of age [11][12][13][14][15][16] . For the most part, the target populations were children with normal development 11,12,15,[17][18][19][20][21][22][23][24][25][26][27][28] or children at-risk for delays 14,16,[29][30][31][32][33][34][35][36] . Two studies included children with confirmed disability diagnoses, such as cerebral palsy 37 and microcephaly 13 .…”
Section: What Do These Findings Mean?mentioning
confidence: 99%
“…Denver II (21,24,29). many of those studies used the screening tests according to their respective purposes, such as verifying the incidence of suspicion of development delays and searching for relationships between risk factors and developmental outcomes in the infant population.…”
Section: To Analyze the Psychometric Properties Of An Instrumentmentioning
confidence: 99%
See 1 more Smart Citation